THE HEDGES USED BY RONNIE MILLER AND STEVE MILLER DURING SUMMER HOLIDAY IN THE LAST SONG MOVIE - Reinzka Unola; Josefa J. Mardijono (Kata Kita: Journal of Language, Literature, and Teaching, 2013)
This study discussed the types and functions of hedges also some changes of hedges perceived in the using of hedges related to social distance. The Last Song by Nicholas Sparks, were used as the source of data and the data of this study were 16 scenes containing conversation between Ronnie Miller and Steve Miller. The theories used were hedges and its functions by Coates (1996), the types of hedges by Salager-Meyer (1997), and hedges related to social distance by Holmes (1996). There were six types of hedges out of seven types found out by the writer in her data. After analyzing hedges based on the types and functions, the writer also analyzed the changes that can be perceived in using hedges and their functions. The data analysis showed that there were some changes in using hedges related to the functions. The changes of the function may be influenced by social distance between the two characters which is expression of doubt, followed by expression of confidence, searching for the right word and sensitivity of others’ feeling.